Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1039/c0np00053a
|View full text |Cite
|
Sign up to set email alerts
|

Construction of spirolactones with concomitant formation of the fused quaternary centre – application to the synthesis of natural products

Abstract: Polycyclic structures fused at a central carbon are of great interest due to their appealing conformational features and their structural implications in biological systems. Although progress in the development of synthetic methodologies towards such structures has been impressive, the stereoselective construction of such quaternary stereocentres remains a significant challenge in the total synthesis of natural products. This review highlights the progress in the formation of 1-oxaspiro[4.n]alkan-2-ones (2≤n≤7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(39 citation statements)
references
References 159 publications
0
24
0
Order By: Relevance
“…Recognizing this useful synthetic approach, we recently reported a palladium‐free Sonogashira reaction to access such γ‐alkylidenebutenolides in a diastereoselective manner5 and we have demonstrated their utility for the construction of spirolactones through Diels–Alder6 or domino7 reactions. However, despite such potential, the versatility of cycloaddition reactions onto conjugated γ,δ double bonds, thereby leading to the formation of fused quaternary stereocenters, remains relatively unexplored 8. Notably, the spiro[6.4] ring system is a recurrent structural motif in numerous natural products (e.g., micrandilactone B and lancifodilactone F).…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing this useful synthetic approach, we recently reported a palladium‐free Sonogashira reaction to access such γ‐alkylidenebutenolides in a diastereoselective manner5 and we have demonstrated their utility for the construction of spirolactones through Diels–Alder6 or domino7 reactions. However, despite such potential, the versatility of cycloaddition reactions onto conjugated γ,δ double bonds, thereby leading to the formation of fused quaternary stereocenters, remains relatively unexplored 8. Notably, the spiro[6.4] ring system is a recurrent structural motif in numerous natural products (e.g., micrandilactone B and lancifodilactone F).…”
Section: Introductionmentioning
confidence: 99%
“…The enantioselective oxidative dearomatization of phenols and their analogues is a key reaction for the synthesis of several natural products 1. Conventionally, enantioselective transition‐metal catalysis has been used for these transformations 1c–e. Recently, some research groups2 have reported catalytic enantioselective oxidative dearomatization reactions using chiral hypervalent iodine compounds 3.…”
Section: Methodsmentioning
confidence: 99%
“…These spirocycles moiety by and large found in various biologically active natural products and clinical pharmaceuticals (Kotha et al, 2009;Bartoli et al, 2011). Beside the biological importance, these spirocycles have been extensively used for the synthesis of novel ligands, catalysts and some special organic optoelectronics synthetic materials (Saragi et al, 2007;Xie and Zhou, 2008;Ding et al, 2009).…”
Section: Introductionmentioning
confidence: 99%